Fabrication of renewable resource based hyperbranched epoxy nanocomposites with MWCNT-polyaniline nanofiber-carbon dot nanohybrid as tough anticorrosive materials - A. Saikia; N. Karak (eXPRESS Polymer Letters)
Multi walled carbon nanotube (MWCNT)-polyaniline nanofiber-carbon dot (CD) nanohybrid was fabricated using in-situ polymerization of aniline in the presence of MWCNT and CD. Different spectroscopic techniques like Fourier transform infrared spectroscopy (FTIR) and ultraviolet-visible (UV-vis) spectroscopy were used to study the formation of the nanohybrid. The obtained nanohybrid was incorporated in different weight percentages in the hyperbranched epoxy derived from renewable resources like sorbitol and monoglyceride of castor oil. The formation of the nanocomposites was also verified using spectroscopic, microscopic and diffraction techniques. The thermosetting nanocomposites with uniform and stable dispersion of nanohybrid demonstrated excellent mechanical properties, such as tensile strength (69 MPa), elongation at break (45%), scratch resistance (>10 kg) and impact resistance (16.7 kJ/m); good thermal stability (above 264 °C) and high chemical resistance. The anticorrosion performances of the cured nanocomposites were studied on mild steel plates in 3.5% sodium chloride (NaCl) solution using potentiodynamic polarization method. The study showed that the nanocomposites with the highest percentage of the nanohybrid exhibited better anticorrosion performance (corrosion rate of 4.62・104 mpy) compared to the pristine thermoset. Thus, this study revealed that the hyperbranched epoxy with stable dispersion of the nanohybrid based nanocomposite can be potentially applied as a high performance anticorrosive material.